2018
DOI: 10.1016/j.jecp.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

It’s all relative: The role of object weight in toddlers’ gravity bias

Abstract: Work over the past 20 years has demonstrated a gravity bias in toddlers; when an object is dropped into a curved tube, they will frequently search at a point immediately beneath the entry of the tube rather than in the object's actual location. The current study tested 2- to 3½-year-olds' (N = 88) gravity bias under consideration of object weight. They were tested with either a heavy or light ball, and they had information about either one of the balls only or both balls. Evaluating their first search behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
4
6
0
Order By: Relevance
“…In summary, it can be noted that object weight alone is not sufficient to impact their search behavior. As in other studies that relied on non-relational object variable comparisons in hidden displacement tasks, such as size (Gresham, 2012) and weight (Hast, 2018), the present study revealed no differences in performance between the two non-relational conditions.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In summary, it can be noted that object weight alone is not sufficient to impact their search behavior. As in other studies that relied on non-relational object variable comparisons in hidden displacement tasks, such as size (Gresham, 2012) and weight (Hast, 2018), the present study revealed no differences in performance between the two non-relational conditions.…”
Section: Discussionsupporting
confidence: 81%
“…However, toddlers had only been given opportunity to explore and see one of the two balls. This seems to be in accordance with Hast’s (2018) observation that object variables might only have an impact on search behavior when children are provided with opportunities for direct experience of contrasting examples of a variable, such as heaviness and lightness.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations